Assessment of social capital to internationalize educational institutions - Jabeen, Mussarat; Umar, Muhammad; Batool, Rubeena; Yasmeen, Kokeb (Othman Yeop Abdullah (OYA) Graduate School of Business, Universiti Utara Malaysia, 2015)
Social capital promotes internationalization and competitiveness.Prevalent notions to measure Internationalization content of organizations are ill with ‘social capital’.Social capital is the core competency in knowledge-based organizations. This paper uses the Leif Edvinsson’s scheme of Intellectual Capital (IC) as the basis of analysis; because the IC causes change in the internationalization content.The particular concern of this paper is to assess and enhance the social capital in the internationalization content of the COMSATS Institute of Information Technology (CIIT system), Pakistan, based on measured behavioral actions by utilizing Knowledge, Attitude, Practice, (KAP) Analysis technique.The internationalization content of CIIT system is characterized by Internationalization Academic Staff (IAS) and Non Internationalization Academic Staff (NIAS). IAS was found more responsive to the questionnaire.The results showed that IAS was having more internationalization knowledge.The attitude of both IAS and NIAS was positive and the practices were found to be more positive among IAS.The social capital exists at 65% as grand mean of the survey showed. Recommendations are offered on how the social capital can be built, thereby to enhance the CIIT system’s capacity to learn, adapt and internationalize in the marketplace.